2016
DOI: 10.1515/helmin-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and host-parasite interrelationship ofHysterothylacium aduncum(Nematoda) in whitingMerlangius merlangusoff the southern and northern coasts of the Black Sea

Abstract: SummaryIn the present study, we investigated the comparative infection levels, ecology and host-parasite interrelationship of a nematode Hysterothylacium aduncum (Rudolphi, 1802) in whiting, Merlangius merlangus (L., 1758) in southern (Sinop) and northern (Balaklava Bay) coasts of the Black Sea for the fi rst time. Fish were collected throughout a period from May 2011 to March 2014 from local fi shermen. A total of 690 fi sh specimens near Sinop and 423 fi sh near Balaklava Bay were examined for parasites. Hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…While all parasitic genera belonging to the phylum Nematoda should be identified in or on the internal organs of their fish hosts, such as the intestine, some genera were identified on the skin mucus ( Acanthocheilus , Dichelyne , Cystidicola , Hysterothylacium and Aonchotheca ) and also on gills ( Contracaecum , Cucullanus , Cystidicola and Aonchotheca ). Among parasitic nematodes, some have an indirect life cycle, which means that they need several successive hosts to complete their life cycle and reach the adult stage [70,76,129]. This is the case for seven genera of nematodes found in the present study, identified on the gills or skin of fish (Table 3): the intermediate host is usually a crustacean (isopods, amphipods, copepods, decapods) and the final host is a teleost [69,76,130134].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all parasitic genera belonging to the phylum Nematoda should be identified in or on the internal organs of their fish hosts, such as the intestine, some genera were identified on the skin mucus ( Acanthocheilus , Dichelyne , Cystidicola , Hysterothylacium and Aonchotheca ) and also on gills ( Contracaecum , Cucullanus , Cystidicola and Aonchotheca ). Among parasitic nematodes, some have an indirect life cycle, which means that they need several successive hosts to complete their life cycle and reach the adult stage [70,76,129]. This is the case for seven genera of nematodes found in the present study, identified on the gills or skin of fish (Table 3): the intermediate host is usually a crustacean (isopods, amphipods, copepods, decapods) and the final host is a teleost [69,76,130134].…”
Section: Discussionmentioning
confidence: 99%
“…Among parasitic nematodes, some have an indirect life cycle, which means that they need several successive hosts to complete their life cycle and reach the adult stage [70,76,129]. This is the case for seven genera of nematodes found in the present study, identified on the gills or skin of fish (Table 3): the intermediate host is usually a crustacean (isopods, amphipods, copepods, decapods) and the final host is a teleost [69,76,130134]. Sequences identified on the skin mucus or on gills may then correspond to larval stages or eggs of nematodes, contained in crustaceans that could have been on the fish's surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the anchovy, the situation may not be as good for the cold-water species of the Black Sea, such as sprat, or for the other fish like turbot and whiting that feed on anchovy and therefore expected to have a higher level of infection due to trophic amplification. As a matter of fact, in the earlier studies conducted in the Black Sea, infections found in sprat (Avşar, 1997) and whiting (İşmen and Bingel, 1999;Özer et al, 2016) were considerably higher than the values observed for anchovy.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, one was identified as H. aduncum and the other Phylogenetic tree clearly indicated that all observed Hysterothylacium isolates clustered together with same species in monophyletic groups supporting of high bootstrap values over 92% (Fig. 1) [4][5][6][7]9,10,[28][29][30][31] . [6] and Zeus faber [8] .…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are approximately 70 recognizable Hysterothylacium species around the world [3] ; however, only two species, H. aduncum and H. fabri, have been morphologically or molecularly described in different fish species from Turkish waters [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%